Nutritional and Health Values of Tunisian Edible Oils from Less-Used Plant Sources - Vadalà, Rossella; Nava, Vincenzo; Turco, Vincenzo Lo; Potortì, Angela Giorgia; Costa, Rosaria; Rando, Rossana; Ben Mansour, Hedi; Ben Amor, Nawres; Beltifa, Asma; Santini, Antonello; Di Bella, Giuseppa (Agriculture (Basel), 2023)
The reclaim of less-used plant sources is a novel approach to the growing demand for healthy and eco-friendly foods, and it constitutes a sustainable alternative to replace conventional food ingredients and sources of bioactives. In this work, a phytochemical profile in terms of mineral elements, total polyphenols, fatty acids, α-tocopherol, sterols, and squalene was realized for several commercial edible oils of bitter almond, pumpkin seed, apricot kernel, nigella, souchet, and wheat germ sourced in the Tunisian market. Wheat germ oil, which showed the most significant nutritional and healthy impact, contained the highest contents of Mg (52.37 mg kg−1); Na (40.75 mg kg−1); Mn (2.39 mg kg−1); total sterols (1713.80 mg/100 g); and PUFAs (61.01%). The high levels of squalene detected on pumpkin seed oils (1160.01 mg kg−1) allows to proposet it as valuable functional food. The highest total polyphenolic content found in nigella oils (109.01 mg GAE kg−1) justifies its stability and antioxidant properties. A daily consumption of 10 g of bitter almond or souchet oil contributes to a 17.53% and 8.6% alpha-tocopherol daily intake, respectively. The usual consumption of these minor oils may represent a sustainable and convenient source of bioactives with beneficial effects on both human health and nutrition.